Bit by Bit: Colocation and the death of distance in software developer networks - Moritz Goldbeck (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
Digital tools potentially enable remote collaboration. Analyzing how some 191 thousand software developers in the United States collaborate on the largest online opensource code repository platform, I find 79.8% of users clustering in only ten economic areas. Conditional on economic-area characteristics, colocated users collaborate about nine times as much as non-colocated users. Apart from this colocation effect, distance is not significantly related to collaboration among software developers. Comparison to social networks shows the colocation effect is weaker for software developers and relative connectedness probability remains at a much higher (stable) level with increasing distance. Software developer and social networks show no significant regional overlap.
Keywords: L84; O18; O30; R32; 330; Geography; digitization; online; open-source; high-skilled; collaboration